Modern technologies in teaching speaking - Egamberdiyeva Marxabo (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This thesis explores the role of modern technologies in teaching speaking skills in English language classrooms. In today’s digital world, the use of various technological tools such as mobile apps, video conferencing platforms, and interactive software has become an effective method to enhance students’ speaking abilities. The paper discusses how these tools provide more opportunities for practice, improve motivation, and offer instant feedback. It also highlights the challenges teachers and students may face when using technology and suggests practical solutions. The findings suggest that when used properly, modern technologies can significantly improve the process of teaching and learning speaking skills.